Pengaruh Penerapan model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Matematika Siswa SMP - Rasyid Izgar; Rismayani Armin (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The objective of this research was to find out the effect of problem based learning learning model application on learning outcome VII grade students of SMP Negeri 1 Siompu Barat at first semester school year 2021/2022. Data collection in this research was carried out using research instrument in the form of learning outcome test and students’ activity observation sheet. Data obtained were analized using statistical analysis and inferential analysis. Based on the result of the research obtained conclusion that: (1) the result of pre-test showed that mean score of students’ mathematics learning outcome was 22.23 from ideal score 100 standard deviation was 8.431; (2) the result of post-test showed that mean score of students’ mathematics learning outcome was 86.47 From ideal score 100 with standard deviation was 7.487; and (3) based on the students’activity percentage during process could be concluded that students’ activity was on category very active with mean score 93.11% and students’ response on problem based learning model was on positive category with the percentage of mean score was 82,1%. It could be concluded that whether the application of problem based learning model affected learning outcome of class VII A students of SMP Negeri 1 Siompu Barat.